A CONCEPTUAL DESIGN OF NEUTRON COLLIMATOR IN THE THERMAL COLUMN OF KARTINI RESEARCH REACTOR FOR IN VITRO AND IN VIVO TEST OF BORON NEUTRON CAPTURE THERAPY - Nina Fauziah; Andang Widiharto; Yohannes Sardjono (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2013)
Studies were carried out to design a collimator which results in epithermal neutron beam for IN VITRO and IN VIVO of Boron Neutron Capture Therapy (BNCT) at the Kartini research reactor by means of Monte Carlo N-Particle (MCNP) codes. Reactor within 100 kW of thermal power was used as the neutron source. The design criteria were based on recommendation from the International Atomic Energy Agency (IAEA). All materials used were varied in size, according to the value of mean free path for each material. MCNP simulations indicated that by using 5 cm thick of Ni as collimator wall, 60 cm thick of Al as moderator, 15 cm thick of 60Ni as filter, 2 cm thick of Bi as γ-ray shielding, 3 cm thick of 6Li2CO3-polyethylene as beam delimiter, with 1 to 5 cm varied aperture size, epithermal neutron beam with maximum flux of 7.65 x 108 n.cm-2.s-1 could be produced. The beam has minimum fast neutron and γ-ray components of, respectively, 1.76 x 10-13 Gy.cm2.n-1 and 1.32 x 10-13 Gy.cm2.n-1, minimum thermal neutron per epithermal neutron ratio of 0.008, and maximum directionality of 0.73. It did not fully pass the IAEA’s criteria, since the epithermal neutron flux was below the recommended value, 1.0 x 109 n.cm-2.s-1. Nonetheless, it was still usable with epithermal neutron flux exceeding 5.0 x 108 n.cm-2.s-1. When it was assumed that the graphite inside the thermal column was not discharged but only the part which was going to be replaced by the collimator, the performance of the collimator became better within the positive effect from the surrounding graphite that the beam resulted passed all criteria with epithermal neutron flux up to 1.68 x 109 n.cm-2.s-1.Keywords: design, collimator, epithermal neutron beam, BNCT, MCNP, criteria Telah dilakukan penelitian tentang desain kolimator yang menghasilkan radiasi netron epitermal untuk uji in vitro dan in vivo pada Boron Neutron Capture Therapy (BNCT) di Reaktor Riset Kartini dengan menggunakan program Monte Carlo N-Particle (MCNP). Reaktor pada daya sebesar 100 kW digunakan sebagai sumber neutron. Kriteria desain berdasar pada rekomendasi dari IAEA. Setiap material divariasikan ukurannya berdasarkan mean free path radiasi di dalam material tersebut. Simulasi MCNP menunjukkan bahwa dengan menggunakan 5 cm Ni sebagai dinding kolimator, 60 cm Al sebagai moderator, 15 cm 60 Ni sebagai filter, 2 cm Bi sebagai perisai sinar-γ, 3 cm 6Li2CO3-polietilen sebagai penahan radiasi neutron, pada variasi bukaan sebesar 1 sampai 5 cm, dihasilkan fluks neutron epitermalmaksimum sebesar 7,65 x 108 n.cm-2.s-1. Radiasi neutron epitermal tersebut memiliki komponen neutron cepat sebesar 1,76 x 10-13 Gy.cm2.n-1, komponen sinar-γ sebesar1,32 x 10-13 Gy.cm2.n-1, rasio neutron termal per netron epitermal sebesar 0,008, dan direksionalitas maksimum sebesar 0,73. Hasil ini masih tidak memenuhi seluruh kriteria IAEA, karena fluks netron epitermal kurang dari 1,0 x 109 n.cm-2.s-1. Meski demikian, radiasi netron epitermal tersebut masih dapat digunakan karena fluksnya melebihi 5,0 x 108 n.cm-2.s-1. Pada saat diasumsikan bahwa bagian kolom termal yang tersisa di luar daerah kolimator tetap berisi grafit seperti semula, hasil keluaran kolimator menjadi lebih baik dengan fluks neutron maksimum mencapai 1,68 x 109 n.cm-2.s-1. Kata kunci : desain, kolimator, radiasi neutron epitermal, BNCT, MCNP, kriteria